2002
DOI: 10.1128/aem.68.12.6029-6035.2002
|View full text |Cite
|
Sign up to set email alerts
|

Photoreactivation of Escherichia coli after Low- or Medium-Pressure UV Disinfection Determined by an Endonuclease Sensitive Site Assay

Abstract: Photoreactivation of Escherichia coli after inactivation by a low-pressure (LP) UV lamp (254 nm), by a medium-pressure (MP) UV lamp (220 to 580 nm), or by a filtered medium-pressure (MPF) UV lamp (300 to 580 nm) was investigated. An endonuclease sensitive site (ESS) assay was used to determine the number of UV-induced pyrimidine dimers in the genomic DNA of E. coli, while a conventional cultivation assay was used to investigate the colony-forming ability (CFA) of E. coli. In photoreactivation experiments, more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
100
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(111 citation statements)
references
References 27 publications
9
100
2
Order By: Relevance
“…This study shows that the dimer repair rates of photolyase decreased when exposed to both LP and MP UV radiation in vitro, an observation that differs from results of Oguma et al (10), who did not detect any change in the activity of MP UV-exposed photolyase. This could be because of the higher dimer concentration in the substrate used in this study and the lack of interferences from other photoproducts, which allowed for more sensitive detection of photolyase activity.…”
contrasting
confidence: 91%
“…This study shows that the dimer repair rates of photolyase decreased when exposed to both LP and MP UV radiation in vitro, an observation that differs from results of Oguma et al (10), who did not detect any change in the activity of MP UV-exposed photolyase. This could be because of the higher dimer concentration in the substrate used in this study and the lack of interferences from other photoproducts, which allowed for more sensitive detection of photolyase activity.…”
contrasting
confidence: 91%
“…Nevertheless, clues are given in some papers that deal with the photoreactivation after irradiation with lowand medium-pressure UV sources [14,15,25]. The general conclusion in these papers is that the survival ratio of the bacteria after photoreactivation following medium-pressure lamps is smaller than that of low-pressure lamps.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no studies have investigated DNA repair in E. coli O157:H7 following MP UV and only limited conflicting studies have evaluated repair following LP UV exposure in water (Tosa & Hirata 1999;Sommer et al 2000;Mofidi et al 2002). Recent studies performed using non-pathogenic E. coli have indicated differences in the repair following low doses of MP and LP UV irradiation (Oguma et al 2002;Zimmer & Slawson 2002). These studies showed that LP and MP UV demonstrated similar levels of inactivation, however, following MP UV exposure DNA repair was greatly reduced.…”
Section: Introductionmentioning
confidence: 99%